La cámara de gesell como mecanismo para evitar la revictimización, en la recepción de los testimonios anticipados en los delitos sexuales en el año 2015, en la fiscalía provincial de Chimborazo, cantón Riobamba - Chinchi Jara, Ana Belén (2018)
Victimization is a process by which a person suffers the consequences of a traumatic event, damage caused by a criminal offense, the victim has to face a set of personal inquiries, in his intervention in a criminal process, this concept includes the effects traumatizing derived from versions, testimonies, forensic examinations, forensic medical examination or the same contact in the trial with the victimizer, which leads the victim to revictimization. Therefore, we will address important issues such as: sexual crimes, anticipated testimonies, procedures and application made in the Gesell Chamber, rights of victims and rights of the accused. The Gesell chamber as a mechanism to prevent the revictimization of victims of sexual crimes the chamber has been a mechanism of great relevance when receiving the anticipated testimony in sexual crimes, since it helps to avoid that the rights of the victim are violated , primarily for constituting a means of proof, carrying out a due process to have as a result that the crime does not remain unpunished, but also without forgetting the rights of the victimizer so that it does not lead to the nullity of the process in the future.